Analisis Ekonomi Propinsi Gorontalo Evaluasi Kebijakan Pemekaran Wilayah - Imamudin Yuliadi; Heri Kurniawan Marpaung (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2010)
In the reformation era is signed by shifting role policy from central government to local government. South Sulawesi is one district at east Indonesia have so many potensial resources to increase the economic welfare. But in the other side they have several problem and constraint to utilize the natural and human resources. One of the main problem to promote east Indonesia economy is how to increase economic potential such as small business enterprise (SBE), informal economic sector, cooperative, agriculture, trade, and any others. Investment is the machine to generate the Indonesian economy. The policy to promote investment is caused with political will and public administration. To promote foreign and domestic investment in province south Sulawesi facing plenty of factor mainly social politic condition, sufficiently of economic infrastructure, employment and taxation problem, ect. Investment in south Sulawesi is also caused by consistenly interaction between local government and central government and among government institution. The aim of this research is to identify and analyse the potensial sector at province south Sulawesi. This research is identify and compare the impact of public policy to economic performance at province south Sulawesi. The research use multimethod analysis to answer the goals of this research. The conclusion of this research that there are several economic that have many constraint and problem. The main problem to promote economic performance at provinsi south Sulawesi mainly infrastructure, financial assestment, managerial skill, marketing, quality control and networking. The suggestion of this research is how to promote the condusive circumstance with comprehensive economic policy and also support with keeping social politic stability, sufficiently of economic infrastructure and the wholism policy between central and local government and others government institution.